Nxopaxopo wa nkucetelo wa ndhavuko eka vutlhokovetseri bya Magaisa, J.M. na Marhanele, M.M. ehenhla ka vavasati - Baloyi, E.M. (My University, 2013)
This research focuses on the analysis of poems on the portrayal of women by the two Xitsonga poets: Magaisa, J.M., Mihloti and Xikolokolo Nguvu, ya Pitori and Marhanele, M.M. Vumunhu bya Phatiwa and Swifaniso swa Vutomi. The main focus will be on the influence of Xitsonga culture on their portrayal of women, basing the argument on what the Constitution of the Republic of South Africa of 1996 says. In Chapter 1, there is a problem statement, aims of the study, rationale for the study, the significance of the study, the methodology, referring to the collection of data, where there is a primary and secondary research methods, scope and delimitation of the study and the literature review. The focus on Chapter 2 is on the explanation of what culture is, that each culture has the good and the bad in it, no culture is static. Chapter 3 focuses on the techniques employed by the poets in their portrayal of women. The focus in Chapter 4 is on the functions of poetry, basing on different eras, that is, the apartheid and democratic South Africa. The analysis of the selected poems will be dealt with in Chapter 5, divided into the married and the unmarried women. Chapter 6 focuses on places where women are discriminated against. Chapter 7 is a conclusion of the dissertation, and also look at what can be done to alleviate this discrimination.
An Analysis of the Influence of culture on the portrayal of Women by the poets Magaisa, J.M. and Marhanele, M.M.
Thesis (M.A. (African Languages)) -- University of Limpopo, 2013
Keywords: Poems; Portrayal of women; Xitsonga poets; Tsonga (African people); Tsonga poetry; African literature - History and criticism